Multi-ethnic SULT1A1 copy number profiling with multiplex ligation-dependent probe amplification. (23rd May 2018) - Vijzelaar, Raymon; Botton, Mariana R; Stolk, Lisette; Martis, Suparna; Desnick, Robert J; Scott, Stuart A
Aim: To develop a SULT1A1 multiplex ligation-dependent probe amplification assay and to investigate multi-ethnic copy number variant frequencies.Methods: A novel multiplex ligation-dependent probe amplification assay was developed and tested on 472 African–American, Asian, Caucasian, Hispanic and Ashkenazi Jewish individuals.Results: The frequencies of atypical total copy number (i.e., greater or less than two) were 38.7% for Hispanics, 38.9% for Ashkenazi Jewish, 43.2% for Caucasians, 53.6% for Asians and 64.1% for African–Americans. Heterozygous SULT1A1 deletion carriers (slow sulfators) were most common among Caucasians (8.4%), whereas African–Americans had the highest frequencies of three or more copies (rapid sulfators; 60.9%).Conclusion: Different ethnic and racial populations have varying degrees of SULT1A1-mediated sulfation activity, which warrants further research and that may have utility for drug response prediction among SULT1A1-metabolized medications.